ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN DENGAN AGENCY COST SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR PERIODE 2019-2022 - Elvira Engelyne; Ivonny; Riny; Eni Duwita Sigalingging (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This research aims to test and analyze the influence of Tax Avoidance, Leverage, Company Size, Liquidity, Capital Structure and Dividend Policy on Company Performance with Agency Cost as a Moderating Variable. The population of this research is 287 manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample in this research used by the author is 144. The data analysis technique used is quantitative analysis using structural equation models with the Smart Pls program by the external model, model feasibility and internal model. The results of the analysis show that Tax Avoidance, Company Size, Liquidity and Dividend Policy partially have no influence Company Performance while Leverage and Capital Structure partially influence Company Performance in manufacturers companies listed on the Indonesian Stock Exchange for the 2019-2022 period. Agency Cost unable to moderate the relationship between Tax Avoidance, Leverage, Company Size, Liquidity and Dividend Policy and Company Performance. While Agency Cost is able to moderate the relationship between Capital Structure and Company Performance in manufacturing companies listed Indonesia Stock Exchange for the 2019-2022 period.